Evaluación de los efectos de la contaminación atmosférica y el ángulo de exposición sobre la corrosión del acero de bajo carbono y acero galvanizado en la región del Valle Central Occidental (VCO) de Costa Rica - Rodríguez Yáñez, Javier E. (2023)
Costa Rica is a country that imports its metallic materials, this makes the evaluation of its corrosion losses of special interest, since they represent an average of 3% of the GDP. In particular, atmospheric corrosion is more than 50% of these losses, so their evaluation in basic metallic materials is a necessity. In this sense, the Western Central Valley (WCV) is the area with the largest population and economic activity in Costa Rica, so the development of this analysis in this area is a priority. This thesis proposes the estimation of the values of atmospheric corrosion for WCV for low carbon steel (like A36) and galvanized iron, as the main consumer products at the country level for the construction of metallic structures. The evaluations were based on the ISO 9223 and associated standards, both for the corrosion process and for the climate and main atmospheric pollutants evaluation during a 24-month period. The pollution levels are low, so the corrosion is controlled mainly by atmospheric parameters, especially the time of wetting (TOW). Furthermore, the corrosion corresponds to a C2 level for both materials. The study proposes a series of meteorological maps associated with the area, as well as annual corrosion maps derived from these, and a proposal of the variability established for the different angles of inclination in steel. The information is complemented for steel with the characterization of the oxides formed, through surface analysis by electron microscopy and X-ray diffraction. As well as their basic analysis by electrochemical techniques.